2007
DOI: 10.1095/biolreprod.107.062752
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Expression of Messenger RNAs Encoding GDF9, BMP15, TGFBR1, BMPR1B, and BMPR2 During Follicular Development and Characterization of Ovarian Follicular Populations in Ewes Carrying the Woodlands FecX2W Mutation1

Abstract: Woodlands sheep have a putative genetic mutation (FecX2(W)) that increases ovulation rate. At present, the identity of FecX2(W) is unknown. The trait does not appear to be due to the previously described mutations in bone morphogenetic protein 15 (BMP15), growth differentiation factor 9 (GDF9), or bone morphogenetic protein receptor type 1B (BMPR1B) that affect ovulation rate in sheep. Potentially, FecX2(W) could be an unidentified genetic mutation in BMP15 or in the closely related GDF9, which interacts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 30 publications
6
55
0
1
Order By: Relevance
“…Our findings confirmed observations made in the pig, sheep, goat and cow in which BMPR1A, BMPR1B and BMPR2 mRNA and/or protein were expressed in the oocyte and in both GC and TC of antral follicles (Wilson et al 2001, Souza et al 2002, Glister et al 2004, Quinn et al 2004, Fatehi et al 2005, Silva et al 2005, Feary et al 2007). …”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings confirmed observations made in the pig, sheep, goat and cow in which BMPR1A, BMPR1B and BMPR2 mRNA and/or protein were expressed in the oocyte and in both GC and TC of antral follicles (Wilson et al 2001, Souza et al 2002, Glister et al 2004, Quinn et al 2004, Fatehi et al 2005, Silva et al 2005, Feary et al 2007). …”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 91%
“…The expression of TGFBR1 mRNA has only been studied in antral follicles of mouse, sheep and cow ovaries, and, consistent with our findings, was expressed in the oocyte, GC and TC (Juneja et al 1996, Juengel et al 2004, Feary et al 2007). Similar to the observations made for the ligands in our study, the oocyte was found to abundantly express BMPR1A, BMPR1B, BMPR2 and TGFBR1 mRNA but little variation in mRNA abundance was observed between the different time points.…”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 89%
“…A possible mechanism for these interactions was identified when it was shown that BMP15 mRNA levels were decreased in animals carrying the Woodlands gene (Feary et al 2007) or homozygous for the Booroola gene (Crawford et al 2011) compared with their wild-type contemporaries. However, BMP15 mutations have also been observed in flocks carrying other putative major genes influencing ovulation rate wherein the effect is additive rather than synergistic.…”
Section: R113mentioning
confidence: 99%
“…Whether GDF9 acts directly on the oocyte to induce follicle growth, indirectly through the granulosa cell or both, is not clear, given that both granulosa cells and oocytes in primary follicles express ALK5 [57][58][59][60][61] and BMPR2 [58,62], the reported type I [63,64] and II receptors for GDF9 [65], respectively. However, it is controversial whether ALK5 is the only type I receptor for GDF9 as Alk5 conditional knockout mice have no defects in follicular development and cumulus expansion [62], which is a distinct phenotype from Gdf9 null mice [17].…”
Section: Discussionmentioning
confidence: 99%